المفردات الاصطلاحية في كتاب فقه المعاملات المالية المعاصرة لإثراء اللغة - Rifaldi J. Dg. Solang; Mohamed El Mustafa (Rayah Al-Islam, 2018)
Arabic is a language rich in vocabulary and terms. The meaning, the purposing and the using have developed and expanded over time. These terms have a close connection with the syar'i sciences, because the syar'i sciences have terms as intermediaries to understand these sciences. Therefore, there needs to be a study of these terms, especially the terms fiqh muamalat al-maliyah al-muashiroh. This study aims to help students of Arabic to know the terms in the book of Fiqh al-Muamalat al-Maliyah al-Muashiroh, and also understanding the meaning correctly. And The method used in this study is descriptive analysis method, namely by tracing the terms of fiqh of contemporary financial transactions in the book. This study proves the existence of terms in Fiqh al-Muamalat al-Maliyah al-Muashiroh, and the number of these terms reaches 40 words. This study also proves that these terms can be used to enrich the language of students through the examples that have been proposed, namely by making a table by stating the meaning of each term accompanied by an explanatory picture of the meaning. Or by making it in conversation and reading texts accompanied by practice questions.